The effects of practice and practice-preparation types of assignment on chemistry achievement - Lopez, Ofelia Laguio
There is a never-ending search for effective teaching devices that will improve teaching and learning outcomes. Assignments are tested instruments that contribute to students improved learning outcomes. However, assignments remain an area of confusion and conflict for many teachers. The author conducted the study to determine the effects of two types of assignment on chemistry achievement.